PreCall : a visual interface for threshold optimization in ML model selection - Christoph Kinkeldey and Claudia Müller-Birn and Tom Gülenman and Jesse Josua Benjamin and Aaron Halfaker (Center for Open Science (OSF), 2019)
Supporting parameter selection for the ORES machine learning as a service. Result-driven view on parameters.